ANALISIS JABATAN APARATUR PEMERINTAH DI LINGKUNGAN SEKRETARIAT DAERAH KABUPATEN SEKADAU - Paratih E.42009063, Elponsa Septi (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
This thesis is mainly intended for consideration for Trustees Personnel officials in addressing the staffing problems that exist in the District Secretariat Sekadau. The title of this thesis was appointed as still there is a mismatch between the results of the job analysis and placement Echelon IV is the presence of vacant positions. This research uses descriptive type of research through qualitative paradigm. selected descriptive qualitative research to understand and provide guidance on issues that will be examined in this regard that the Government of the Job Analysis Apparatus echelon IV in Environmental Secretariat Sekadau regency, with research subjects Sekadau District Secretary, Office of the Chief of Personnel and Training Sekadau District, head of Secretariat of the Organization of Regional and Sub-Section Head of Organization Formation and Anjab Sekadau District Regional Secretariat.Conclusion of this research is the analysis of the position is not in accordance with job requirements: rank / class space, education, and training in the office. for it is in the understanding of job analysis of government officials should apply the principle of the right man on the right place to achieve government professional, neutral and accountable, and prosperous.Â Keywords: job analysis, job requirements, and job suitability.